2020
DOI: 10.1016/s0140-6736(19)32008-2
|View full text |Cite|
|
Sign up to set email alerts
|

Modifiable risk factors, cardiovascular disease, and mortality in 155 722 individuals from 21 high-income, middle-income, and low-income countries (PURE): a prospective cohort study

Abstract: Modifiable risk factors for cardiovascular disease and mortality (26•3% of the PAF), although the single largest risk factor was a low education level (12.5% of the PAF). Ambient air pollution was associated with 13•9% of the PAF for CVD (although different statistical methods were used for this analysis). In MIC and LIC, the importance of household air pollution, poor diet, low education, and low grip strength were larger compared with HIC.Interpretation: The majority of CVD cases and deaths can be attributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
922
7
65

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 1,288 publications
(1,026 citation statements)
references
References 29 publications
32
922
7
65
Order By: Relevance
“…Third, consistent with the changing epidemiology of CVD vs. cancer mortality [29], there were likely cohort effects within our broad study period, with higher CVD death rates among participants enrolled earlier in our study. This likely explains, at least partly, why CHD and CVD mortality in CAC = 0 drifted down with time over our study, while cancer mortality rose.…”
Section: Study Limitationssupporting
confidence: 57%
See 1 more Smart Citation
“…Third, consistent with the changing epidemiology of CVD vs. cancer mortality [29], there were likely cohort effects within our broad study period, with higher CVD death rates among participants enrolled earlier in our study. This likely explains, at least partly, why CHD and CVD mortality in CAC = 0 drifted down with time over our study, while cancer mortality rose.…”
Section: Study Limitationssupporting
confidence: 57%
“…In addition, a key strength and novel contribution to the CAC = 0 literature is the use of competing risk Fine and Gray modelling, which provides more accurate estimates of causespecific risk in the presence of competing events in prognostic studies. Recent international epidemiological data have shown that cancer deaths have become twice as frequent as CVD deaths in developed countries [29], which stresses the need to appropriately account for competing risks with cancer death in cardiovascular epidemiological analyses in Western countries.…”
Section: Discussionmentioning
confidence: 99%
“…As expected [36], we observed a significant reduction in plasma Vitamin D concentrations. Deficient vitamin D concentrations (< 80) were observed in 8 (67%) participants after deployment, as compared to 2 (17%) before deployment.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, we observed lower urinary concentrations of calcium and potassium indicating increased re-absorption of these minerals in the kidneys, which may compensate for low intestinal absorption. In a French cohort [36], deployment onto a submarine induced Vitamin D-deficiency and impaired bone remodeling. In contrast, no effects of submarine deployment, or rather some improvements, were observed on bone mass or strength in another study [6], designed to determine the effect of 400 IU/d-Vitamin D supplementation in 53 US Submariners.…”
Section: Discussionmentioning
confidence: 99%
“…Using these data, quintiles of usual consumption were created based on the dietary intake of seven food groups that are considered healthy: fruits, vegetables, nuts, legumes, fish, dairy, and meats (chicken and red meats) . This was based on the Prospective Urban Rural Epidemiological (PURE) dietary quality score that has been validated in several studies and where a higher “PURE healthy diet score” was associated with a clear reduction in mortality, cardiovascular disease, myocardial infarction, and stroke overall, and in those with and without vascular disease or diabetes . For the current analysis, participants were divided into quintiles by consumption level for each food group category, with the lowest quintile representing the highest level of consumption.…”
Section: Methodsmentioning
confidence: 99%